2023
DOI: 10.3390/molecules28083450
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Pyrimidine- and Coumarin-Linked Hybrid Molecules as Inducers of JNK Phosphorylation through ROS Generation in Breast Cancer Cells

Abstract: Human epidermal growth factor receptor 2 (HER2)-positive breast cancer exhibits early relapses, poor prognoses, and high recurrence rates. Herein, a JNK-targeting compound has been developed that may be of utility in HER2-positive mammary carcinoma. The design of a pyrimidine-and coumarin-linked structure targeting JNK was explored and the lead structure PC-12 [4-(3-((2-((4-chlorobenzyl)thio) pyrimidin-4-yl)oxy)propoxy)-6-fluoro-2H-chromen-2-one (5d)] was observed to selectively inhibit the proliferation of HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…72 ) was found to selectively impede the proliferation of HER2-positive BC cells. 134 It induced DNA damage and apoptosis in HER-2-positive BC cells more effectively compared to HER-2 negative BC cells. In silico and theoretical calculations revealed that compound 75 could interact with c-Jun N-terminal kinase (JNK), and in vitro studies showed that it increased JNK phosphorylation through ROS generation.…”
Section: Coumarin Hybridsmentioning
confidence: 93%
“…72 ) was found to selectively impede the proliferation of HER2-positive BC cells. 134 It induced DNA damage and apoptosis in HER-2-positive BC cells more effectively compared to HER-2 negative BC cells. In silico and theoretical calculations revealed that compound 75 could interact with c-Jun N-terminal kinase (JNK), and in vitro studies showed that it increased JNK phosphorylation through ROS generation.…”
Section: Coumarin Hybridsmentioning
confidence: 93%
“…HT‐29, SW480, HCT‐116, and HCT‐15 cells (2 × 10 4 cells/well) were seeded onto the 8‐well slide chamber and they were exposed to 30 μM of CBD for 24 h. These cells were used to perform the live and dead assay as indicated before 34 …”
Section: Methodsmentioning
confidence: 99%
“…The four cell lines were treated with 30 μM of CBD for 24 h and then were stained with fluorescein isothiocyante‐tagged Annexin‐V antibodies and PI for 15 min. The rate of apoptotic cells was detected by BD Accuri TM C6 Plus Flow Cytometer (BD Biosciences) 34 …”
Section: Methodsmentioning
confidence: 99%
“…EPBS was treated for 12 h and the cells were collected. A total of 10 µM of DCFH-DA was treated for 30 min at 37 °C, and the samples were analyzed using a BD Accuri TM C6 Plus Flow Cytometer (BD Biosciences) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that NAC can prevent oxidative stress and promote the activity of antioxidant enzymes [ 31 ]. GSH is oxidized in the presence of ROS and converted to GSSG, which can prevent oxidative stress [ 32 ].…”
Section: Introductionmentioning
confidence: 99%